(3GdhSjW aj TQM bGfhf GdLRGA GdYeGfj (B:s (3GdbSe GdNGU (B: (3GdLQGFe GdhGbYI Ydi GdCaQGO (B= Mediator in the explanation of Omani penal law : private section : crimes against individuals /s - (3YHjO, eRgQ LYaQs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2014)
(3SHb dj hCf CdaJ cJGHG aj ehVhYGJ GdLQGFe GdhGbYI Ydi GdCaQGO aj bGfhf GdLRGA GdYeGfj, EdG Cfg HYO EYGOI GdfXQ ajg hLOJ Cfg de jZW, hHGdbOQ GdcGaj, eG jJYdb HJdc GdLQGFe ef eSGFd, aBKQJ Cf CUOQ eDdaG LOjOG, hHeSei eNJda, hgh jMjW HGdbhGYO GdbGfhfjI GdJj LQeJ GdCaYGd GdJj JfGd ef MjGI GdaQO hSdGeI LSOg hYQVg hMQjJg hcQGeJg(B. (3hef CLd EfLGR eG YReJ GdCeQ Ydjg, abO JWQbJ Edi GdLQGFe GdJj fU YdjgG JMJ YfhGf (B((3aj GdLQGFe GdhGbYI Ydi GdCaQGO(B)(3, hEdi Gdege ef GdLQGFe GdJj LGAJ Vef eSei (B((3aj GdLQGFe GdeNdI HGdYQV hGdCNdGb GdYGeI(B)(3, hJdc GdJj hQOJ JMJ JHhjH (B((3aj GdLQGFe GdeQJcHI VO GdMQjI GdTNUjI hGdTQa(B)(3, heG jQJHW HgG ef LQGFe CNQi, LGA PcQgG Vef LQGFe GdehXajf, cLQjeI MLR MQjI GdCaQGO JYSaG(B. (3hfJjLI deG Je HMKg ef LQGFe, CUHM gPG GdeDda eJejRG Yf SGHbg, aj fhY hce GdehVhYGJ GdJj LQi JfGhdgG YHQ eaQOGJg, hCVMi HPGJ GdhbJ, eJhGabG eY YfhGfg GdehShe H` (B((3GdhSjW aj TQM bGfhf GdLRGA GdYeGfj, GdbSe GdNGU, GdLQGFe GdhGbYI Ydi GdCaQGO(B).s
(3JUeje (B: (3GdKbGaI ddJUeje hGdENQGL(B.s
(3HHdjhLQGajI (B: (3UaMI (B441-448.s
Keywords: (3GdbGfhf GdLfGFjs -- (3YeGf (B((3SdWfI(B)s; (3LQGFe VO GdCTNGUs -- (3bhGfjf hJTQjYGJs -- (3YeGf (B((3SdWfI(B)s; (3bGfhf GdYbhHGJs -- (3YeGf (B((3SdWfI(B)s